2019
DOI: 10.1093/conphys/coz028
|View full text |Cite
|
Sign up to set email alerts
|

Mapping physiology: biophysical mechanisms define scales of climate change impacts

Abstract: The rocky intertidal zone is a highly dynamic and thermally variable ecosystem, where the combined influences of solar radiation, air temperature and topography can lead to differences greater than 15°C over the scale of centimetres during aerial exposure at low tide. For most intertidal organisms this small-scale heterogeneity in microclimates can have enormous influences on survival and physiological performance. However, the potential ecological importance of environmental heterogeneity in determining ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 182 publications
(265 reference statements)
2
38
0
Order By: Relevance
“…However, mineralogy is just one potential driver of the temperature differences identified here. Differences in colour (Raimondi, 1988;Marshall, McQuaid & Williams, 2010;Judge, Botton & Hamilton, 2011) and microtopography (Lathlean, Ayre & Minchinton, 2012;Choi et al, 2019) have been shown previously to affect rock temperature, with the six rock types investigated here also differing in these attributes. It is possible that the smooth, featureless surfaces of siltstone were able to reach hotter surface temperatures versus the coarse, textured surfaces of limestone and quartzite.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…However, mineralogy is just one potential driver of the temperature differences identified here. Differences in colour (Raimondi, 1988;Marshall, McQuaid & Williams, 2010;Judge, Botton & Hamilton, 2011) and microtopography (Lathlean, Ayre & Minchinton, 2012;Choi et al, 2019) have been shown previously to affect rock temperature, with the six rock types investigated here also differing in these attributes. It is possible that the smooth, featureless surfaces of siltstone were able to reach hotter surface temperatures versus the coarse, textured surfaces of limestone and quartzite.…”
Section: Discussionmentioning
confidence: 54%
“…For example, temperature mosaics were generally observed on quartzite boulders only. These temperature mosaics may have developed because of the specific microtopographic features of quartzite (i.e., coarse, angular surfaces), with microtopography associated with temperature heterogeneity on rocky seashores elsewhere ( Lathlean, Ayre & Minchinton, 2012 ; Choi et al, 2019 ). Alternatively, these mosaics may reflect differences in long-wave emissivity not accounted for by our use of a generic emissivity value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developing new models restarts the iterative process to test whether the additional physiological mechanisms better inform our understanding of what limits species distributions and how species are responding to novel abiotic pressures during climate‐induced shifts. Ultimately, physiological studies of non‐climatic abiotic factors can help shape ecological theory, as has proven particularly fruitful in intertidal communities (Choi et al 2019).…”
Section: A Roadmap To Advancing the Science Of Global Change Biology mentioning
confidence: 99%